Small Bowel Cocoon: A Distinct Disease with a New Developmental Etiology - Ibrahim E. Bassiouny; Tariq O. Abbas (Case Reports in Surgery)
We have treated two patients with small bowel (abdominal) cocoon who presented with acute and partial small bowel obstruction associated with an abdominal mass. Neither had a history of previous surgery, peritonitis, or prolonged drug therapy. The distinct features of this disease are illustrated. A developmental etiology and a new nomenclature for this disease are proposed, along with a review of the literature.